"Tattooed Collage" - A Perspective of Youth Culture - Alexander, Ellen (Journal of youth and theology, 2004)
In this article, Ellen Alexander seeks to reassess the nature of Youth Culture, with specific reference to youth in India. This paper was originally given at the IASYM Pune Conference, November 2004.